Examining The Unseen: Rare Homicide at Unusual Spot with Unusual Injury (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
male with an unusual firearm entry wound on the surface of  the small intestinal loop, which was surgically exposed (open laparotomy wound),  causing extensive internal damage and hemorrhage. The bullet recovered from  the subcutaneous plane on the right side of the abdomen. The death was due to  hemorrhagic shock caused by a firearm injury to the internal abdominal organs. What sets this case apart in the literature is not just the tragic nature of the event but  the context in which it occurred—a hospital, a place inherently associated with safety  and healing. In the landscape of forensic and medical literature, this case stands out  because of the intersection of violence and healthcare, which challenges the norms of  both fields. This incident highlights the critical need for enhanced security measures  in hospitals to prevent violence against patients and doctors. This examination not  only provides crucial insights into the nature of gunshot wounds and their impact  on internal organs but also emphasizes the broader implications for hospital security  and patient safety.
Keywords: Firearm injury; Bullet Trajectory; Hospital violence; Entry wound artefact